Pengaruh Brand Awareness Dan Brand Image Terhadap Loyalitas Pelanggan Telkomsel - Putri Amanta, Aulia; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
Telkomsel as the largest telecommunications company in Indonesia also faces challenges in retaining its customers amidst the increasing number of communication service providers offering a variety of choices. The purpose of this study is to analyze the influence of Brand Image and Brand Awareness on Telkomsel Customer Loyalty. The population is all Telkomsel users in Indonesia. This study is a quantitative study using data sources, namely primary data obtained by filling out questionnaires distributed through Google Form. The sample in this study consisted of 150 respondents with a sampling technique, namely non-probability sampling with a purposive sampling method. The analysis tool used in this study is Smart PLS 3.0. The hypotheses in this study include the first Brand Awareness has a significant influence on Customer Loyalty. The second hypothesis is that Brand Image has a significant influence on Customer Loyalty.